Study of Surface Tension Properties looked on Contact Angle Value on 100% Nylon Textile Fabric Using Corona Discharge Plasma Technology - Valentinus Galih Vidia Putra; Juliany Ningsih Mohamad; Yusril Yusuf (Wahana Fisika, 2020)
This paper provides an explanation of the application of corona discharge plasma in textile field specially for modification  of surface properties and wet ability of nylon 100% fabric. In this research, we have found that the properties of  wet ability of nylon 100% fabric with 70 / inch of weft density and 60/inch of warp density  is influenced by  corona discharged plasma analyzed by the contact angle of the fabric on capillarity phenomena under same test time for contact angle test.       Artikel ini menjabarkan  pemanfaatan aplikasi teknologi plasma pijar korona pada bidang tekstil dalam modifikasi sifat pembasahan pada permukaan kain nilon 100% ditinjau dari sifat fenomena kapilaritas. Hasil riset memperlihatkan bahwa dengan perlakuan plasma pada kain nilon 100% dengan tetal pakan dan lusi masing-masing 70 helai/inci dan 60 helai/inci didapatkan  bahwa terdapat perubahan sifat hidrofilik (dapat lebih mudah menyerap) kain melalui perubahan sudut kontak pada fenomena kapilaritas untuk waktu uji sudut kontak yang sama.